Aetiology of sudden cardiac death in athletes in the United Kingdom: a pathological study. Issue 17 (13th May 2009) - de Noronha, S V; Sharma, S; Papadakis, M; Desai, S; Whyte, G; Sheppard, M N
Abstract : Objective: To characterise the demographics and aetiology of sudden cardiac death (SCD) in athletes referred to a tertiary cardiac pathology centre in the UK. Design: Retrospective non-case controlled analysis. Setting: Cardiac pathology centre at the National Heart and Lung Institute and Royal Brompton Hospital. Subjects: Between 1996 and 2008, the hearts of 118 athletes were referred for pathological assessment to ascertain the precise aetiology of SCD. Results: The majority of athletes (n = 113; 96%) were male and most (107; 91%) were amateurs participating predominantly in football, rugby and running. The mean (SD) age of death was 28 (12) years (range 7–59); 75% athletes were aged ⩽35 years. Most deaths (81%) occurred during or immediately after exercise. Antecedent symptoms of cardiac disease were reported in 21 (18%) subjects, and 20 (17%) had a family history of premature cardiovascular disease and/or SCD. 25 (21%) athletes had relevant past medical history which included a known history of cardiac disease. Cardiomyopathy was the commonest cause of death and accounted for 62% of all the SCDs. A significantly high proportion of athletes (23%) exhibited a morphologically normal heart. Atherosclerotic coronary disease accounted for only 3% of cases and was confined to athletes aged >35 years. Conclusions: SCD in sport is largely due to clinically silent cardiomyopathies or primary electrical disorders (morphologically normal heart). Antecedent symptoms and family history are absent in over 80% of cases, and therefore clinical screening with health questionnaires will fail to identify most athletes with potentially sinister cardiac disorders.